Disclosing the nature of vacancy defects in α-Ag2WO4 - Assis, M. (2023)
Defects at semiconductors with electron acceptor and donor sites govern the electronic and optoelectronic applications due to their unique electronic properties. This work provides deep insight into the nature of defects and the conduction mechanism in α-Ag2WO4. To this aim, a detailed analysis of the results of XRD with Rietveld refinements, FE-SEM images, and measurements of different spectroscopies (impedance, positron annihilation lifetime, and photoluminescence) are carried out on α-Ag2WO4 samples synthesized by a simple co-precipitation method. Two types of vacancy defects: cationic O-vacancies, and anionic Ag or Ag–O vacancy complexes are elucidated with a Schottky p-type potential barrier. The results indicate that the Ag vacancies remain constant during thermal treatment, while an opposite effect is found for the oxygen vacancies. This behavior governs the multifunctional properties of α-Ag2WO4 semiconductors via a tunneling plus thermionic conduction mechanism.